Insights from a systematic review of literature on social enterprise and networks: Where, how and what next?. Issue 4 (5th November 2018) - Littlewood, David; Khan, Zaheer
Abstract : Purpose: This paper aims to contribute to better understanding of where and how network concepts, theories and perspectives, organisational networks, and networking practices, are being studied and deployed in social enterprise research. This is done through a systematic review of social enterprise and networks literature in business and management journals. Key trends and developments in this literature, and gaps and limitations, are identified, culminating in discussion of what next for social enterprise and networks research. The papers in this special issue on "Social Enterprise and Networks" are introduced. Design/methodology/approach: A systematic review was undertaken of social enterprise and networks literature in business and management journals. Journals sampled included all those in the Entrepreneurship and Small Business subject area of the Association of Business Schools (ABS) Academic Journal Guide 2018, the journals in the Financial Times 50 research ranking, and selected wider business and society, non-profit management and public administration journals. Findings: Analysis of publishing patterns of social enterprise and networks research finds that such research is growing, and that varied network perspectives, concepts and theories are being deployed. Social enterprise and networks are also being studied globally, using different methodologies. Nevertheless, there remains scope for deeper theoretical engagement, and for a wider range of network theories to be used. More even geographic coverage is also needed, and further insights can be gained through use of alternative methodologies. Research limitations/implications: Discussions in this paper have implications for research through outlining systematically the state of current scholarship on social enterprise and networks. In so doing, insight is provided on what is known about social enterprise and networks. But also on what is not known and where further enquiry is needed. Direction is thus provided for future social enterprise and networks scholarship. Practical implications: In this paper, how, and the extent to which, social enterprise and networks scholarship offers implications for practice and policy is considered. Originality/value: This paper makes a valuable contribution to social enterprise scholarship. It outlines the state of current knowledge and research on social enterprise and networks, identifying where and how relationships between social enterprise and networks have been studied, whilst also providing insights for what next in future social enterprise and networks research.